The current state and topical directions of vegetation research of National Nature Park «Dzharylgachsky» (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The article deals with current state of research of vegetation of national park «Dzharylgachsky». The results of floristic, geobotanic and fitosozologic research since the beginning of 20th century are presented. Digression into history of conservation of the area is done. The relevance of further studies of vegetation in the park is Considered, namely − сlarification of floral component, development of the classification scheme and prodromus of vegetation, investigation of syndynamic processes.
Keywords: history of research, vegetation, conservation, Dzharylgach.